Low-loss temperature-stable microwave dielectric ceramic and dielectric resonant antenna thereof
Patent Information
- Application Number
- CN202611207051.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-11-03
AI Technical Summary
现有岩盐结构微波介电陶瓷在谐振频率温度系数调控过程中存在τf调控幅度有限、复相易导致品质因数显著劣化、温度补偿调控机理不明确的问题,难以满足5G/6G无线通信器件的应用需求。
Li2TiO3 was used as the temperature coefficient compensation phase and combined with Li2.5Mg2.5Ti0.5Nb0.5O12 in a two-phase composite process. Through the dual synergistic regulation of component ratio and crystal structure, the directional adjustment of τf was achieved. Low-loss temperature-stable microwave dielectric ceramics were prepared by solid-state reaction method.
While achieving a near-zero resonant frequency temperature coefficient, it maintains a high Q×f value. The fabrication process is simple and controllable. The ceramic dielectric resonator antenna exhibits high gain, low loss, and good temperature stability in the C-band and 5G/6G communication bands.
Smart Images

Figure CN123026439A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of microwave dielectric ceramics and dielectric resonant antennas, specifically to a low-loss temperature-stable rock-salt structure microwave dielectric ceramic, its solid-state reaction preparation method, and a dielectric resonator antenna based on the ceramic, which can be applied to microwave devices such as filters and resonant antennas in 5G / 6G wireless communication systems. Background Technology
[0002] Microwave dielectric ceramics are a key fundamental material in modern wireless communication systems, widely used in microwave devices such as dielectric resonators, filters, and resonant antennas. Practical engineering applications require microwave dielectric ceramics to possess a suitable dielectric constant (ε). r ), quality factor (Q×f), and temperature coefficient of near-zero resonant frequency (τ) f This ensures the performance stability of the device over a wide temperature range.
[0003] Among various microwave dielectric ceramics, rock salt structures have attracted widespread attention due to their intrinsically high Q×f values and strong compositional tunability. Series ceramics such as Li₂AO₃-MgO (A = Ti, Zr, Sn) and Li₃MO₄-MgO (M = Nb, Ta) have been systematically studied. However, these materials generally suffer from problems such as a negative temperature coefficient of resonant frequency and a high sintering temperature, making it difficult to meet the temperature stability requirements of devices and limiting their further practical applications.
[0004] τ f A common compensation strategy is to combine two τ values. f The recombination of phases with opposite signs makes the system's τ f Towards zero value control. However, traditional two-phase composite methods are prone to problems such as incompatibility of crystal structures between phases, intensified interface polarization, and increased dielectric loss, which lead to a significant deterioration of the material's Q×f value, making it impossible to simultaneously achieve synergistic optimization of low loss and temperature stability.
[0005] Currently, rock salt structured microwave dielectric ceramics still face many technical bottlenecks: τ f Limited control range, re-phase easily leading to significant degradation of quality factor, and unclear temperature compensation control mechanism make it difficult to meet the application requirements of next-generation wireless communication devices such as 5G / 6G in terms of overall performance. Summary of the Invention
[0006] The purpose of this invention is to provide a low-loss, temperature-stable microwave dielectric ceramic and its preparation method, and to provide a dielectric resonator antenna based on this ceramic, aiming to achieve a near-zero resonant frequency temperature coefficient while maintaining a high Q×f value, and with a simple and controllable preparation process.
[0007] In the existing positive τ fAmong the compensating materials, Li₂TiO₃ shares the same crystal structure as most rock salt ceramics, exhibiting good structural compatibility. This invention selects Li₂TiO₃ as the temperature coefficient compensating phase for two-phase composite formation. Through the dual synergistic regulation of component ratio and crystal structure, it is possible to achieve τ without significantly degrading the quality factor. f Targeted adjustment.
[0008] To solve the above problems, the present invention adopts the following technical solution:
[0009] This invention provides a low-loss, temperature-stable microwave dielectric ceramic with a rock-salt structure, having the chemical formula (1-x)Li. 2.5 Mg 2.5 Ti 0.5 Nb 0.5 O 12 -xLi2TiO3, abbreviated as (1-x)LMTN-xLT, where x is the molar coefficient, with a value range of 0.2 ≤ x ≤ 0.85.
[0010] When 0.2 ≤ x ≤ 0.75, the ceramic has a single-phase cubic rock salt structure with a space group of Fm-3m. When 0.8 ≤ x ≤ 0.85, the ceramic has a two-phase coexistence structure, with the main phase being a cubic rock salt structure MgO phase and the second phase being a monoclinic structure Li2TiO3 phase. When x = 0.8, the ceramic achieves a near-zero temperature coefficient of resonant frequency, specifically: temperature coefficient of resonant frequency τ f = -8.3 ppm / °C, dielectric constant ε r = 17.07, quality factor Q×f = 76,546 GHz.
[0011] This invention provides a method for preparing the above-mentioned low-loss temperature-stable rock-salt structure microwave dielectric ceramic, which is prepared by solid-state reaction method, and the specific steps are as follows:
[0012] Step 1: According to the general chemical formula (1-x)Li 2.5 Mg 2.5 Ti 0.5 Nb 0.5 O 12 The stoichiometric ratio of Li2CO3, MgO, Nb2O5, and TiO2 raw materials for -xLi2TiO3 is as follows:
[0013] Step 2: Mix the raw materials weighed in Step 1 with anhydrous ethanol and then ball mill them;
[0014] Step 3: Dry the mixed slurry obtained from ball milling in Step 2 to obtain a dried mixed powder;
[0015] Step 4: The dried mixed powder obtained in Step 3 is kept at 1000°C for 4 hours to obtain pre-calcined powder;
[0016] Step 5: The pre-calcined powder obtained in Step 4 is ball-milled a second time, dried, and then granulated with a binder.
[0017] Step 6: Press the granulated powder obtained in Step 5 into a shape to obtain a green body;
[0018] Step 7: The green body obtained in Step 6 is held at 600°C for 2 hours to remove the binder, and then sintered at a temperature range of 1280°C to 1360°C for 4 hours. It is then allowed to cool naturally in the furnace to obtain microwave dielectric ceramic. The optimal sintering temperature is adjusted according to the composition: the optimal sintering temperature is 1340°C when x = 0.2, and 1320°C when 0.4 ≤ x ≤ 0.85.
[0019] This invention provides a dielectric resonator antenna, fabricated using a low-loss, temperature-stable ceramic obtained at x = 0.8. The antenna structure includes: an FR4 substrate (a glass fiber reinforced epoxy resin copper-clad laminate with a relative permittivity of approximately 4.4), a metal microstrip feed line, and a ceramic dielectric resonator (DR) radiator. The antenna has a center frequency of 5.72 GHz (C-band) and a return loss (Si). 11 The lowest gain is -40.2 dB, the maximum gain is 6.22 dBi, the highest radiation efficiency is 95.53%, and the cross-polarization suppression ratio is greater than 40 dB. It can be applied to C-band (4-8 GHz) and 5G / 6G microwave communication bands.
[0020] Compared with the prior art, the present invention has the following advantages:
[0021] (1) Performance Synergistic Optimization: This invention uses Li2TiO3, which belongs to the same rock salt structure system as the matrix, as the temperature coefficient compensation phase. Utilizing the compatibility of the two-phase crystal structures, it avoids the interfacial polarization and loss degradation problems caused by phase mismatch in traditional heterogeneous composites. When τ f When adjusted to near zero (x = 0.8), τ f While maintaining a high Q×f value (76,546 GHz) (-8.3 ppm / °C), it achieves a synergistic balance among dielectric constant, quality factor and temperature coefficient.
[0022] (2) Flexible component control: The ceramic system described in this invention has a wide adjustable range of components (0.2 ≤ x ≤ 0.85), and the performance evolution laws of the single-phase region (x ≤ 0.75) and the two-phase region (x ≥ 0.8) are clear. By adjusting the x value, the dielectric constant (14.92~18.03) and temperature coefficient (-30.2~+10.5 ppm / °C) can be directionally controlled to meet the performance requirements of different microwave devices.
[0023] (3) Simple and controllable process: The present invention is prepared by traditional solid-state reaction method, which does not require complicated equipment or special atmosphere conditions. The sintering temperature is moderate (1280~1360 °C), and the parameters of each process are stable and controllable, which makes it easy to realize large-scale industrial production.
[0024] (4) Excellent device performance: The dielectric resonator antenna based on the ceramic fabrication of this invention has a center frequency of 5.72 GHz (C-band) and a return loss S 11 With a gain as low as -40.2 dB, a maximum gain of 6.22 dBi, a radiation efficiency of 95.53%, and a cross-polarization rejection ratio greater than 40 dB, the ceramic of this invention effectively supports the antenna to achieve high-gain, high-efficiency, and high-purity polarization radiation performance while ensuring temperature stability. This makes it suitable for applications in C-band satellite communication and 5G / 6G wireless communication systems with stringent requirements for bandwidth selectivity and signal quality. Attached Figure Description
[0025] Figure 1 These are the X-ray diffraction patterns of the (1-x)LMTN-xLT ceramics of Examples 1-6 of this invention at the optimal sintering temperature;
[0026] Figure 2 These are scanning electron microscope (SEM) images of the (1-x)LMTN-xLT ceramics of Examples 1-6 of this invention;
[0027] Figure 3 These are density and microwave dielectric property curves of (1-x)LMTN-xLT ceramics in Examples 1-6 of the present invention, where (a) is the curve of relative density as a function of component x, (b) is the curve of dielectric constant as a function of component x, (c) is the curve of quality factor as a function of component x, and (d) is the curve of temperature coefficient of resonant frequency as a function of component x.
[0028] Figure 4 This is a temperature characteristic curve of dielectric constant and dielectric loss of the ceramic in Embodiment 3 of the present invention;
[0029] Figure 5 This is a three-dimensional structural model diagram of the dielectric resonator antenna designed based on Embodiment 5 (0.2LMTN-0.8LT ceramic) of the present invention;
[0030] Figure 6 These are simulation and test results of the dielectric resonator antenna designed based on Embodiment 5 (0.2LMTN-0.8LT ceramic) of the present invention, where (a) is S 11 Figure 1 shows the return loss curve, (b) shows the gain and radiation efficiency curve, (c) shows the three-dimensional radiation pattern, (d) shows the radiation pattern of the E-plane, and (e) shows the radiation pattern of the H-plane. Detailed Implementation
[0031] The technical solution of the present invention will be further described in detail below with reference to specific embodiments, but the scope of protection of the present invention is not limited to the content described.
[0032] A low-loss, temperature-stable microwave dielectric ceramic with a rock-salt structure, having the general chemical formula (1-x)Li. 2.5 Mg 2.5 Ti 0.5 Nb 0.5 O 12 -xLi₂TiO₃, abbreviated as (1-x)LMTN-xLT, where x is the molar coefficient, ranging from 0.2 ≤ x ≤ 0.85. The microwave dielectric ceramic exhibits a disordered cubic rock salt single-phase crystal structure within the range of 0.2 ≤ x ≤ 0.75, and a composite phase of disordered cubic MgO and ordered monoclinic Li₂TiO₃ within the range of 0.8 ≤ x ≤ 0.85. Its phase transition range is as follows: Figure 3 As shown. The Li content can be controlled by changing the value of component x. + Mg 2+ Ti 4+ 、Nb 5+ The proportion of cations can be used to directionally regulate the microwave dielectric properties of ceramics.
[0033] Example 1: 0.8LMTN-0.2LT microwave dielectric ceramic (x = 0.2)
[0034] The specific preparation steps are as follows:
[0035] Step 1: Weigh the raw materials, Li2CO3, MgO, Nb2O5, and TiO2, with a purity ≥ 99.9%, according to the stoichiometric ratio;
[0036] Step 2: First ball milling. Add the raw material powder, anhydrous ethanol and zirconium balls to the ball mill jar in a mass ratio of 1:1.5:2. Ball mill at 400 r / min for 8 hours. Place the resulting slurry in an 80℃ constant temperature oven to dry for 3 hours.
[0037] Step 3: Place the ball-milled and dried powder into a muffle furnace and heat it to 1000°C at a rate of 5 °C / min. Hold the temperature for 4 hours to obtain pre-calcined powder.
[0038] Step 4: The pre-calcined dry powder is ball-milled a second time, granulated by adding 5% PVA solution, passed through an 80-mesh sieve, and then pressed into a cylindrical green body with a length of 12 mm and a width of 6 mm under a pressure of 20 MPa.
[0039] Step 5: The green body is first pre-fired at 600 °C at 3 °C / min for 2 hours to remove the binder, and then sintered at 1340 °C at 5 °C / min for 4 hours.
[0040] The X-ray diffraction pattern of Example 1 is as follows: Figure 1 As shown, comparison with the MgO standard card (JCPDS No. 96-101-1119) confirms that Example 1 has a pure cubic rock salt structure. Its SEM microstructure is as follows. Figure 2 As shown in (a), the grain boundaries in Example 1 are clear and dense, with an average grain size (AG) of 30.68 μm. Figure 3 As shown in (a), the relative density of this Example 1 is 90.2%.
[0041] Example 2: 0.6LMTN-0.4LT microwave dielectric ceramic (x = 0.4). The preparation steps were the same as in Example 1, but the sintering temperature was adjusted to 1320 °C.
[0042] The X-ray diffraction pattern of this embodiment 2 is as follows: Figure 1 As shown, comparison with the MgO standard card (JCPDS No. 96-101-1119) confirms that Example 2 has a pure cubic rock salt structure. Its SEM microstructure is as follows. Figure 2 As shown in (b), the grains are uniformly distributed, with clear and dense grain boundaries, and an average grain size of 28 μm. Figure 3 As shown in (a), the relative density of this Example 2 is 93.3%.
[0043] Example 3: 0.5LMTN-0.5LT microwave dielectric ceramic (x = 0.5). The preparation steps were the same as in Example 1, but the sintering temperature was adjusted to 1320 °C.
[0044] The X-ray diffraction pattern of Example 3 is as follows: Figure 1 As shown, comparison with the MgO standard card (JCPDS No. 96-101-1119) confirms that Example 3 has a pure cubic rock salt structure. Its SEM microstructure is as follows. Figure 2 As shown in (c), the boundaries are clear and dense, with an average grain size of 26.7 μm. Figure 3As shown in (a), the relative density of this Example 3 is 92.9%.
[0045] Example 4: 0.25LMTN-0.75LT microwave dielectric ceramic (x = 0.75). The preparation steps were the same as in Example 1, but the sintering temperature was adjusted to 1320 °C.
[0046] The X-ray diffraction pattern of Example 4 is as follows: Figure 1 As shown, comparison with the MgO standard card (JCPDS No. 96-101-1119) confirms that Example 4 has a pure cubic rock salt structure. Its SEM microstructure is as follows. Figure 2 As shown in (d), the boundaries are clear and dense, with an average grain size of 21.59 μm. Figure 3 As shown in (a), the relative density of this Example 4 is 91.6%.
[0047] Example 5: 0.2LMTN-0.8LT microwave dielectric ceramic (x = 0.8, optimal example). The preparation steps are the same as in Example 1, but the sintering temperature is adjusted to 1320 °C.
[0048] The X-ray diffraction pattern of Example 5 is as follows: Figure 1 As shown, by comparing with MgO and Li₂TiO₃ standard cards, it can be confirmed that the 0.2LMTN-0.8LT ceramic is a multiphase structure with the coexistence of cubic rock salt MgO phase and monoclinic Li₂TiO₃ phase. Its SEM microstructure is shown below. Figure 2 As shown in (e), the grain boundaries are clear and dense, but due to the formation of the second phase, porosity increases, and the average grain size is 19.89 μm. Figure 3 As shown in (a), the relative density of this Example 5 is 90%.
[0049] The temperature dependence of the dielectric constant and dielectric loss in Example 5 is as follows: Figure 4 As shown in Figures (a) and (b), the dielectric temperature spectrum test results show that the dielectric constant and dielectric loss of the sample did not show significant abrupt changes in the range of -40 ℃ to 100 ℃, and the temperature stability is excellent, which can meet the wide temperature range operation requirements of microwave devices.
[0050] Example 6: 0.15LMTN-0.85LT microwave dielectric ceramic (x = 0.85). The preparation steps were the same as in Example 1, but the sintering temperature was adjusted to 1320 °C.
[0051] The X-ray diffraction pattern of Example 6 is as follows: Figure 1 As shown, by comparing with the standard cards for MgO and Li₂TiO₃, it can be confirmed that the crystal structure of the ceramic in Example 6 is a multiphase structure in which MgO and Li₂TiO₃ phases coexist. Its SEM microstructure is shown below. Figure 2As shown in (f), the grain boundaries are clear and dense, but due to the presence of the second phase, porosity increases, and the average grain size is 18.66 μm. Figure 3 As shown in (a), the relative density of this Example 6 is 89.6%.
[0052] The microwave dielectric properties of Examples 1-6 were tested using the Hakki-Coleman method, and the specific test results are shown in Table 1. Microwave dielectric properties (ε) of Examples 1-6 of this invention. r Q×f、τ f The trend of change with x is as follows: Figure 3 As shown in (b)-(d).
[0053] Table 1. Microwave dielectric properties measured in each embodiment.
[0054] Example number Ceramic chemical formula <![CDATA[ε r ]]> Q×f (GHz) <![CDATA[τ f (ppm / °C)]]> Sintering temperature (°C) 1 0.8LMTN-0.2LT 14.92 82,069 -30.2 1340 2 0.6LMTN-0.4LT 15.22 87,429 -28 1320 3 0.5LMTN-0.5LT 15.84 85,067 -22.1 1320 4 0.25LMTN-0.75LT 16.8 82,417 -15.6 1320 5 0.2LMTN-0.8LT 17.07 76,546 -8.3 1320 6 0.15LMTN-0.85LT 18.03 72,287 10.5 1320
[0055] The results of Examples 1 to 6 show that the dielectric constant and temperature coefficient of the ceramic system described in this invention have a wide range of tunability: ε r The value is 14.92~18.03, τ f The temperature coefficient ranges from -30.2 to +10.5 ppm / °C, covering a wide temperature range from negative to positive. This is comparable to typical rock-salt structure ceramics listed in Table 2 (such as Li₂Mg₄TiO₇:τ₂). f = -7.24 ppm / °C, sintering temperature 1600 °C; Li3Mg2NbO6: τ f Compared to (-27.2 ppm / °C, sintering temperature 1250 °C), Example 5 of the present invention (0.2LMTN-0.8LT) achieved τ at a moderate sintering temperature of 1320 °C. f A near-zero temperature coefficient of -8.3 ppm / °C is achieved while maintaining a high quality factor of Q×f = 76,546 GHz and a stable dielectric response. This result fully demonstrates that the present invention employs a crystal structure-compatible two-phase composite strategy, effectively solving the τ-response problem of rock-salt structured ceramics through dual regulation of crystal structure and composition, while maintaining low loss. f Despite the common problem of being biased towards negative performance, its overall performance is superior to most previously reported similar materials.
[0056] Table 2 Microwave dielectric properties of typical rock salt structure microwave dielectric ceramics
[0057] Ceramic chemical formula <![CDATA[ε r ]]> Q×f (GHz) <![CDATA[τ f (ppm / °C)]]> Sintering temperature (°C) <![CDATA[Li6Mg7Ti3O 16 ]]> 15.27 209,400 -11.32 1550 <![CDATA[Li2Mg4TiO7]]> 13.43 233,600 -7.24 1600 <![CDATA[Li2Mg2TiO5]]> 13.4 95,000 -32.5 1320 <![CDATA[Li4MgSn2O7]]> 12.4 58,754 12.1 1180 <![CDATA[Li2Mg3SnO6]]> 8.8 123,000 -32 1360 <![CDATA[Li2Mg3ZrO6]]> 12.6 86,000 -36 1380 <![CDATA[Li3Mg2NbO6]]> 16.8 79,643 -27.2 1250
[0058] Example 7: Design of a High-Gain, High-Efficiency Dielectric Resonant Antenna
[0059] The 0.2LMTN-0.8LT ceramic material prepared in Example 5 was used to fabricate a cylindrical dielectric resonator body, which was then combined with an FR4 metal substrate and a microstrip feed line to obtain a dielectric resonator antenna. The three-dimensional simulation model of the antenna in Example 7 is shown below. Figure 5 As shown in (a), the antenna core dimensions are: FR4 substrate side length (L) is 40 mm, microstrip line length (W_lenth) is 27.15 mm, width (W_wide) is 2.5 mm, and the length (L) of the rectangular slot in the ground plane is... s The diameter is 4.76 mm, and the width (W) is 4.76 mm. s The diameter (R) of the dielectric resonator is 2.87 mm, and its radius (R) is 5.2 mm and height (H) is 5.34 mm. A physical diagram of embodiment 7 is shown below. Figure 5 As shown in (b).
[0060] In this embodiment 7, HFSS was used to simulate and calculate the antenna, and physical testing was conducted. The results are as follows: Figure 6 As shown. Figure 6 (a) shows the return loss curve. The measured center frequency is 5.72 GHz, corresponding to the lowest S... 11 The value is -35 dB; the simulation center frequency is 5.70 GHz, corresponding to the lowest S... 11 The value is -40.2 dB, and the two are in good agreement. Figure 6 (b) shows the gain versus radiation efficiency curves. The gain at the center frequency is 6.22 dBi, and the radiation efficiency is 95.53%. Figure 6 (c) shows the three-dimensional gain pattern. Figure 6 (d) and Figure 6 (e) shows the radiation patterns of the E-plane and H-plane, respectively, with the normal co-polarization component being 46 dB higher than the cross-polarization component.
[0061] The antenna test results in Example 7 further verified that the antenna based on 0.2LMTN-0.8LT ceramic (ε r =17.07, Q×f=76,546 GHz, τ f The dielectric resonant antenna prepared with a temperature of -8.3 ppm / °C exhibits good impedance matching (S0.05) at a center frequency of 5.72 GHz. 11 Radiation characteristics including -40.2 dB, high gain (6.22 dBi), high efficiency (95.53%), and high polarization purity (cross-polarization suppression >40 dB).
[0062] In summary, this invention achieves near-zero temperature coefficient while maintaining low dielectric loss through dual synergistic regulation of composition and crystal structure. The resulting ceramic has promising engineering application prospects in high-performance antenna devices for C-band and 5G / 6G communication bands.
Claims
1. A low-loss, temperature-stable microwave dielectric ceramic, characterized in that, The general chemical formula of the microwave dielectric ceramic is (1-x)Li. 2.5 Mg 2.5 Ti 0.5 Nb 0.5 O 12 -xLi2TiO3, abbreviated as (1-x)LMTN-xLT, where x is the molar coefficient, with a value range of 0.2 ≤ x ≤ 0.
85.
2. The low-loss temperature-stable microwave dielectric ceramic according to claim 1, characterized in that, When 0.2 ≤ x ≤ 0.75, the crystal phase of the microwave dielectric ceramic is a disordered cubic rock salt single phase; when 0.8 ≤ x ≤ 0.85, the crystal phase of the microwave dielectric ceramic is a composite phase of disordered cubic MgO phase and ordered monoclinic Li2TiO3 phase.
3. The low-loss temperature-stable microwave dielectric ceramic according to claim 1, characterized in that, When x=0.8, the temperature coefficient τ of the resonant frequency of the microwave dielectric ceramic is... f =-8.3ppm / ℃, dielectric constant ε r =17.07, quality factor Q×f=76,546GHz.
4. A method for preparing microwave dielectric ceramic as described in claim 1, characterized in that, Includes the following steps: Step 1: According to the general chemical formula (1-x)Li 2.5 Mg 2.5 Ti 0.5 Nb 0.5 O 12 The raw materials Li2CO3, MgO, Nb2O5 and TiO2 were weighed in the stoichiometric ratio of -xLi2TiO3. Step 2: Mix the raw materials weighed in Step 1 with anhydrous ethanol and then ball mill them; Step 3: Dry the mixed slurry obtained from ball milling in Step 2 to obtain a dried mixed powder; Step 4: The dried mixed powder obtained in Step 3 is kept at 1000°C for 4 hours to obtain pre-calcined powder; Step 5: The pre-calcined powder obtained in Step 4 is ball-milled a second time, dried, and then granulated with a binder. Step 6: Press the granulated powder obtained in Step 5 into a shape to obtain a green body; Step 7: The green body obtained in Step 6 is kept at 600°C for 2 hours to remove the binder, and then sintered at a temperature range of 1280°C to 1360°C for 4 hours. It is then naturally cooled in the furnace to obtain microwave dielectric ceramic.
5. The preparation method according to claim 4, characterized in that, In step 2, the mass ratio of raw material powder, anhydrous ethanol and zirconium balls is 1:1.5:
2.
6. The preparation method according to claim 4, characterized in that, In step 7, when x = 0.2, the sintering temperature is 1340°C; when 0.4 ≤ x ≤ 0.85, the sintering temperature is 1320°C.
7. A dielectric resonator antenna, characterized in that, It is prepared using the low-loss, temperature-stable rock salt structure microwave dielectric ceramic described in claim 3.
8. The dielectric resonator antenna according to claim 7, characterized in that, The dielectric resonator antenna includes an FR4 substrate, a metal microstrip feed line, and a ceramic dielectric resonator radiator; the ceramic dielectric resonator radiator is made of the low-loss temperature-stable microwave dielectric ceramic described in claim 3.
9. The dielectric resonator antenna according to claim 8, characterized in that, The center frequency of the dielectric resonator antenna is 5.72 GHz, and the return loss S0 is 5.72 GHz. 11 The minimum gain is -40.2 dB, the maximum gain is 6.22 dBi, the radiation efficiency is 95.53%, and the cross-polarization suppression ratio is greater than 40 dB.
10. The dielectric resonator antenna according to claim 7, characterized in that, The dielectric resonator antenna operates in the C-band and 5G / 6G microwave communication bands.
